Study of Thermodynamic Parameters and Viscosity Behaviour of Substitutent Pyrazoles in 70% dioxane-water. Part-I - V.G. Raut, Ms.; Raghuwanshi, P.B.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
Viscosity measurements have been made on system comprising 3- (2" -hydroxy-3" -nitro-5" -chlorophenyl)-5-(2' -furyl) pyrazoline in 70% dioxane-water mixture solvent at different temperatures. The data have been used to calculate viscosity and thermodynamic parameters such as ΔG*, ΔH*, and ΔS*. We have also studied the effect of solvent on the viscosity at 30°C. It has been found that viscosity increases with increase in the percentage of dioxane. Also viscosity increases due to increase in concentration of ligand in 70% dioxane-water system. In the present investigation we have calculated the value of β-coefficient and other thermodynamic parameters ΔG*, ΔH*, and ΔS* for the ligand which shows that the process is spontaneous and irreversible.